2021
DOI: 10.1177/17455065211065873
|View full text |Cite
|
Sign up to set email alerts
|

Turkish and Moroccan Dutch women’s views of using a self-sampling kit for human papillomavirus testing as a tool for cervical cancer screening: What are the barriers and the motivators?

Abstract: Objective: This study explores barriers and motivators to use self-sampling kits for human papillomavirus testing for cervical cancer screening as perceived by Dutch women of Turkish and Moroccan origin living in the Netherlands. Methods: A total of 11 in-depth semi-structured interviews were conducted and structured according to the theory of planned behavior. Results: Findings suggest that self-sampling may lift important barriers hampering traditional cervical cancer screening, such as those related to sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This is not uncommon, especially in Muslim-dominated societies which value modesty and sexual purity of women. A study conducted in Morocco within a Muslim-dominated community reported that women were reluctant to perform self-sampling for fear of losing their virginity [ 74 ]. The fear of defilement presents a challenge to implementing an HPV self-sampling intervention and warrants extensive culture-sensitive education and awareness.…”
Section: Discussionmentioning
confidence: 99%
“…This is not uncommon, especially in Muslim-dominated societies which value modesty and sexual purity of women. A study conducted in Morocco within a Muslim-dominated community reported that women were reluctant to perform self-sampling for fear of losing their virginity [ 74 ]. The fear of defilement presents a challenge to implementing an HPV self-sampling intervention and warrants extensive culture-sensitive education and awareness.…”
Section: Discussionmentioning
confidence: 99%